EVIDENCE AND CHARACTERISTICS OF HYDROLYTIC DISPROPORTIONATION OF ORGANIC MATTER DURING METASOMATIC PROCESSES - Price L.C.; DeWitt E. (My University, 2001)
Petroleum-geochemical analyses of carbonaceous regionally metamorphosed rocks, carbonaceous rocks from ore deposits, and alkalic plutonic rocks from diverse settings, demonstrated the presence of very low to moderately low concentrations of solvent-extractable organic matter, this observation in spite of the fact that some of these rocks were exposed to extremely high metamorphic temperatures. Biomarker and δ¹³C analyses established that the extractable organic matter originated as sedimentary-derived hydrocarbons. However, the chemistry of the extractable bitumen has been fundamentally transformed from that found in sediment bitumen and oils.